2008
DOI: 10.1177/0042098008090681
|View full text |Cite
|
Sign up to set email alerts
|

Building Social Capital in Hong Kong by Institutionalising Participation: Potential and Limitations

Abstract: This paper draws on ethnographic research in Hong Kong to question the effectiveness of Elinor Ostrom's `design principles' in providing solutions to social divisions by social capital building and institutionalised participation. It challenges the strategic and instrumental assumptions of human motivations for not adequately considering moral concerns, a sense of commitment and the right way of doing things in social cooperation. The tendency to formalise the process of participation, by authority building, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Although Pridmore et al (2007) point out that many forms of social capital can be found globally, Wong (2008) argues that it exists at a very weakened and impoverished level in Hong Kong, and even that social bonding is at "crisis" level in this region. This study warns the government that weakening social networks will create strong reliance of the government in the long run (Wong, 2008(Wong, : 1418. This study warns the government that weakening social networks will create strong reliance of the government in the long run (Wong, 2008(Wong, : 1418.…”
Section: Conceptual Background To the Studymentioning
confidence: 99%
“…Although Pridmore et al (2007) point out that many forms of social capital can be found globally, Wong (2008) argues that it exists at a very weakened and impoverished level in Hong Kong, and even that social bonding is at "crisis" level in this region. This study warns the government that weakening social networks will create strong reliance of the government in the long run (Wong, 2008(Wong, : 1418. This study warns the government that weakening social networks will create strong reliance of the government in the long run (Wong, 2008(Wong, : 1418.…”
Section: Conceptual Background To the Studymentioning
confidence: 99%
“…Women and men themselves have to be responsible for designing and building institutions which appear appropriate and useful to them. Institution building takes time, and it requires strong political will and resources to support local people even after the end of the project (Wong 2008 post-project development in order to build resilient and robust institutions. Third, the success of challenging power inequalities lies in developing sustainable alternative livelihood strategies with local people.…”
Section: Policy Implicationsmentioning
confidence: 99%